Immortal Fetuses - Cutaş, Daniela (Cambridge quarterly of healthcare ethics, 2008)
“Dissecting Bioethics,” edited by Tuija Takala and Matti Häyry, welcomes contributions on the conceptual and theoretical dimensions of bioethics.The section is dedicated to the idea that words defined by bioethicists and others should not be allowed to imprison people's actual concerns, emotions, and thoughts. Papers that expose the many meanings of a concept, describe the different readings of a moral doctrine, or provide an alternative angle to seemingly self-evident issues are therefore particularly appreciated.The themes covered in the section so far include dignity, naturalness, public interest, community, disability, autonomy, parity of reasoning, symbolic appeals, and toleration.All submitted papers are peer reviewed. To submit a paper or to discuss a suitable topic, contact Tuija Takala at tuija.takalahelsinki.fi.